Śaṃkara's Advaita Vedānta : a way of teaching - Suthren Hirst, Jacqueline (RoutledgeCurzon Hindu studies series., 2005)
Samkara (c.700 CE) has been regarded by many as the most authoritative Hindu thinker of all time. A great Indian Vedantin brahmin, Samkara was primarily a commentator on the sacred texts of the Vedas and a teacher in the Advaitin teaching line. This book serves as an introduction to Samkara's thought which takes this as a central theme. The author develops an innovative approach based on Samkara's ways of interpreting sacred texts and creatively examines the profound interrelationship between sacred text, content and method in Samkara's thought. The main focus of the book is on Samkara's te.